1998
DOI: 10.1046/j.1432-1327.1998.2510781.x
|View full text |Cite
|
Sign up to set email alerts
|

Bound water in apo and holo bovine heart fatty‐acid‐binding protein determined by heteronuclear NMR spectroscopy

Abstract: Two-and three-dimensional heteronuclear NMR experiments have been performed to identify internally bound water molecules in the solution structure of bovine heart fatty-acid-binding protein (heart FABP). NOE and rotating-frame NOE (ROE) cross peaks between protein protons and protons of bound water molecules were observed in two-dimensional H 2O-ROE/NOE-1 H, 15 N-heteronuclear single quantum coherence spectra recorded from a uniformly 13 C/ 15 N-enriched sample of bovine heart FABP. Contacts between water prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 1 publication
2
20
0
1
Order By: Relevance
“…Analysis of water diffusion in MD simulations suggests that most water molecules are in a motional regime close to the limit at which protein-water nuclear Overhauser effects are expected to vanish~although this results is for apo I-FABP!. Intriguingly, based on similar NMR experiments, Mesgarzadeh et al 1998! suggested 23 contacts between long-lived, internally bound water molecules in holo bovine H-FABP.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Analysis of water diffusion in MD simulations suggests that most water molecules are in a motional regime close to the limit at which protein-water nuclear Overhauser effects are expected to vanish~although this results is for apo I-FABP!. Intriguingly, based on similar NMR experiments, Mesgarzadeh et al 1998! suggested 23 contacts between long-lived, internally bound water molecules in holo bovine H-FABP.…”
Section: Discussionmentioning
confidence: 96%
“…have been recently reported Mesgarzadeh et al, 1998!. These authors reported long-lived hydration water to be in contact with NH groups of Val84, Val68, and Gly67 in both apo and holo H-FABP, but they did not comment specifically on the position of water molecules which could give rise to these contacts.…”
Section: Detection Of W135 By Nmrmentioning
confidence: 95%
“…17 Cross-relaxation studies of I-FABP hydration were recently completed in our laboratory, 18 and similar studies of related bovine heart fatty acid binding protein (H-FABP) have also been described. 19 In this work, we report three independent one-nanosecond MD simulations of fully solvated apo I-FABP. We analyze the instantaneous number of internal water molecules as a function of the simulation time, evaluate potential pathways for the exchange of internal water molecules, and estimate their mean-square fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…For more than a decade, many researchers have undertaken the challenging task of investigating the mechanisms of interaction between water molecules and globular proteins~Ooi & Oobatake, 1988;Otting et al, 1991aOtting et al, , 1991bHolak et al, 1992;Levitt & Park, 1993;Willams et al, 1994;Alonso & Daggett, 1995;Denisov et al, 1995Denisov et al, , 1999Ernst et al, 1995;Bhattacharjya & Balaram, 1997;Takano et al, 1997;Mesgarzadeh et al, 1998;Shortle, 1999!. Some of these authors have examined the possible role of water as a stabilizing~or destabilizing!…”
mentioning
confidence: 99%
“…Nevertheless, the introduction of multiparametric methods, which are capable of monitoring several different properties during the same experiment, may represent an important step forward in the study of such protein conformations. Multidimensional NMR can provide significant information about where the interaction between water and protein molecules takes place at the protein surface, the quantities of water molecules and protein cavities and lifetimes of the water molecules, among other dynamic characteristics~Willams et Alonso & Daggett, 1995;Denisov et al, 1995;Ernst et al, 1995;Otting, 1997;Mesgarzadeh et al, 1998!. NMR allows us to see almost all the spectral compounds in the sample and to measure nuclear Overhauser effects~NOE!, relaxation times, spinspin couplings, and so on.…”
mentioning
confidence: 99%